2016
DOI: 10.21010/ajtcam.v14i1.22
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical Study of Plants Used to Treat Asthma in the Maritime Region in Togo

Abstract: Background: Asthma is one of the most common chronic diseases in modern society and it is evident that its incidence and severity are increasing, however very little is known about the plants used in the management of the disease. This study therefore aimed to document the plants usage in the Togolese traditional medicine to treat asthma. Methodology: From January to June 2015, an ethnobotanical survey was conducted using a semi-structured questionnaire with traditional healers (THs) in the southern region of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 31 publications
1
9
0
1
Order By: Relevance
“…Our finding with respect to a higher proportion of women than men in traditional medicine practice is similar to that of some previous works [5,8,14,15]. But our results differ from those of Gbekley et al [7] and Gnagne et al [16] who found a higher proportion of men than women. Their results could come from the fact that in their studies, the respondents were only traditional therapists.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our finding with respect to a higher proportion of women than men in traditional medicine practice is similar to that of some previous works [5,8,14,15]. But our results differ from those of Gbekley et al [7] and Gnagne et al [16] who found a higher proportion of men than women. Their results could come from the fact that in their studies, the respondents were only traditional therapists.…”
Section: Discussionsupporting
confidence: 81%
“…According to the WHO, nearly 80% of people in developing countries in Africa use traditional medicine for their health care [2]. Thus, many ethnobotanical surveys have been conducted in many African countries [3,4,5,6] and particularly in Togo [7]. These surveys are aimed at one or more diseases or consist of an inventory of medicinal plants used by the target populations.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that leaves and roots were mostly used for the treatment of asthma [36]. Chi-square was used to compare differences between groups and p value was less than 0.0001 A similar study showed that to treat liver disease, the most used parts of this plant were the leaves and roots, thus extracts of this plant can aid in a broad spectrum of symptoms [37].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an archive of information on herbal medicine from various cultural backgrounds (Indian, Chinese, Japanese, Korean, African and Arabian) for the management and treatment of asthma. [65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81] To date, knowledge on the medicinal plants used for asthma medication and their mode of preparations are limited to some herbal medicine practitioners although some clinical and pharmacological evidences are available. 68 Therefore, there is insufficient evidence to make recommendations to use of these TMPs in clinical practice since the global acceptance and utilisation of herbal medicines is dependent on their safety and efficacy.…”
Section: Challenges and Opportunities Of Tmps For The Treatment Of Asthmamentioning
confidence: 99%